GROWTH REQUIREMENTS OF A HALOPHILIC BLUE-GREEN ALGA, PHORMIDIUM TENUE (MENEGH). - Pillai, V Krishna (Indian Journal of Fisheries, 2016)
IN order to account for the neghgible growth of algas observed in the saline lagoons at Mandapam a complete knowledge of the normal nutritional and general physiological factors controlling the growth of at least the dominant species of the algal association is necessary. This information will also have appUed significance in the maintenance of adequate algal growth, a prerequisite for successful fish culture in these lagoons, regardless of whether or not the fish grown feeds directly on the algae